Probing black hole accretion in quasar pairs at high redshift. Issue 1 (15th March 2018) - Vignali, C; Piconcelli, E; Perna, M; Hennawi, J; Gilli, R; Comastri, A; Zamorani, G; Dotti, M; Mathur, S
Abstract: Models and observations suggest that luminous quasar activity is triggered by mergers, so it should preferentially occur in the most massive primordial dark matter haloes, where the frequency of mergers is expected to be the highest. Since the importance of galaxy mergers increases with redshift, we identify the high-redshift Universe as the ideal laboratory for studying dual AGN. Here, we present the X-ray properties of two systems of dual quasars at z = 3.0–3.3 selected from the SDSS DR6 at separations of 6–8 arcsec (43–65 kpc) and observed by Chandra for ≈65 ks each. Both members of each pair are detected with good photon statistics to allow us to constrain the column density, spectral slope and intrinsic X-ray luminosity. We also include a recently discovered dual quasar at z = 5 (separation of 21 arcsec, 136 kpc) for which XMM – Newton archival data allow us to detect the two components separately. Using optical spectra we derived bolometric luminosities, BH masses and Eddington ratios that were compared to those of luminous SDSS quasars in the same redshift ranges. We find that the brighter component of both quasar pairs at z ≈ 3.0–3.3 has high luminosities compared to the distribution of SDSS quasars at similar redshift, with J1622A having an order magnitude higher luminosity than the median. This source lies at the luminous end of the z ≈ 3.3 quasar luminosity function. While we cannot conclusively state that the unusually high luminosities of our sources are related to their having a close companion, for J1622A there is only a 3 per cent probability that it is by chance.